Going postdigital : presenting and promoting digital art within contemporary digital culture - Grba, Dejan (2020)
The paper discusses the context, the challenges and the new strategies for promoting digital art in contemporary digital culture. The significance of facing challenges and the necessity for new strategies in promoting digital art were the key points at the closing plenary of ISEA 2016 in Hong Kong. We acknowledged that digital art professionals predominantly operate and most efficiently communicate within the limited circles of like-minded artists, authors and cultural workers. Combined with glitches of human cognition such as confirmation bias, framing and heuristic reasoning, this contributes to our prevailing illusion that today digital art is widely recognized, well established and adequately evaluated. Digital art is certainly much more present in contemporary culture and more widely covered by the media than it had ever been before, but it remains a fringe of the art world, of the art market and—most critically—of art education.